Causes of New Cases of Major Thalassemia in Sistan and Balouchistan Province in South-East of Iran - E Miri-Moghaddam; M Naderi; S Izadi; MA Mashhadi (Tehran University of Medical Sciences, 2012)
Background: Thalassemia is the most common monogenic disease in South-East of Iran. Despite the 70% reduction in Iranian thalassemia cases after thalassemia control comprehensive program, 601 affected babies were born in Sistan and Balouchistan Province, Iran from 2002 to 2010, so this study aims at investigating the causes of new thalassemia cases. Methods: Data from this retrospective cross-sectional study was collected through interviews and information in the patients' hospital records. Results: Data revealed that 52.4% of fathers and 78.4% of mothers of thalassemic children had elementary education or less. In addition, 78.6% of the couples did not undergo premarital screening for thalassemia and 71.2% of the couples were not notified of their own minor thalassemia until a child was born with major thalassemia. Of the diagnosed minor couples, about 25% did PND and the others did not carry out because mothers were unaware of proper gestational age and of the importance of this issue, financial problems, and the husbands' disagreement to take the tests. Moreover, 16 mothers, in spite of being diagnosed of having a major fetus, refused to terminate the pregnancy. Conclusion: The most preventable causes for affected births include couples' unawareness of being minor and unawares of the PND importance and process.